2013
DOI: 10.1097/hjh.0b013e3283613053
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, awareness and risk factors of hypertension in a large cohort of Iranian adult population

Abstract: Background There is considerable variation in hypertension prevalence and awareness, and their correlates, across different geographic locations and ethnic groups. We performed this cross-sectional analysis on data from the Golestan Cohort Study (GCS). Methods Enrollment in this study occurred in 2004–2008, and included 50,045 healthy subjects from Golestan Province in northeastern Iran. Hypertension was defined as a systolic blood pressure (SBP) ≥140, a diastolic blood pressure (DBP) ≥90, a prior diagnosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
92
1
14

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(130 citation statements)
references
References 60 publications
23
92
1
14
Order By: Relevance
“…In Golestan province, Iran, a cohort study that analyzed 5 800 elderly individuals over 60 years of age demonstrated that more than half of elderly people had HTN (24). In addition, a review on related published articles between 1996 and 2005 estimated that~50% of Iranian individuals aged > 55 years had HTN that somewhat confirmed our result (26).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In Golestan province, Iran, a cohort study that analyzed 5 800 elderly individuals over 60 years of age demonstrated that more than half of elderly people had HTN (24). In addition, a review on related published articles between 1996 and 2005 estimated that~50% of Iranian individuals aged > 55 years had HTN that somewhat confirmed our result (26).…”
Section: Discussionsupporting
confidence: 77%
“…In addition, studies on elderly populations have been limited to specific areas; therefore, the results might not be generalizable to all Iranian elderly (24,25). Although the prevalence of uncontrolled HTN in Iranian elderly populations could be estimated as 50% based on re- views, the exact prevalence of uncontrolled HTN cannot be concluded for recent years as previous reports were all based on data from prior years (26).…”
Section: Introductionmentioning
confidence: 99%
“…11 The use of an undisciplined hearing protective device at work will also increase the risk of increased blood pressure. 12 Obesity in workers is also at risk of increasing blood pressure than the ideal body weight, 13 more extended time off work (9.6+7.8 years) will be more risky for increased blood pressure because every day the worker is exposed to noise. 14 The objective of this study was to examine the association of risk factors that influence blood pressure increase (age, use of hearing protection, body mass index, and duration of noise exposure) with systolic blood pressure and diastolic blood pressure in textile industry workers in Surakarta.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to noise, several factors that can increase blood pressure in workers in the textile industry are age, 10,11 use of hearing protection devices, 12 bodies mass index, 13 and duration of noise exposure. 12 Increasing age can increase blood pressure especially after 40 years old.…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension has affected 39.5% of the world population (5). The action plan of WHO for prevention and control of non-communicable diseases in 2013 -2020 has aimed at a 25% relative reduction in the prevalence of hypertension (HTN) (6). The increase in the prevalence of HTN in older women causes higher mortality rate than in men, and 60% of the deaths, which are directly associated with hypertension occur in women (7).…”
Section: Introductionmentioning
confidence: 99%